2015
DOI: 10.1016/j.jsps.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Hospital pharmacists’ self-evaluation of their competence and confidence in conducting pharmacy practice research

Abstract: A large proportion of hospital pharmacists in Qatar self-assessed themselves as having deficiencies in several domains of research process or competencies, although they recognized the value of research in advancing pharmacy practice. These findings have important implications for developing informal research training programs and promoting the pursuit of formal postgraduate programs to bridge the knowledge gaps found among hospital-practicing pharmacists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(86 citation statements)
references
References 26 publications
(90 reference statements)
10
76
0
Order By: Relevance
“…Therefore, pharmacy practice research is essential for documenting the evidence of benefit of existing or new services and models of practice [3–5]. However, while research is important to the advancement of pharmacy practice, empirical evidence has demonstrated that pharmacists' involvement in practice research is limited globally [5–15]…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pharmacy practice research is essential for documenting the evidence of benefit of existing or new services and models of practice [3–5]. However, while research is important to the advancement of pharmacy practice, empirical evidence has demonstrated that pharmacists' involvement in practice research is limited globally [5–15]…”
Section: Introductionmentioning
confidence: 99%
“…In the present study 40.7% CP and 55.4% HP participants had previously engaged in practice-based research, most of which were not written up for publication in peer-reviewed or professional journal. Studies have also reported increasing involvement of pharmacists in practice-based research with proportion of pharmacists with research experience ranges from 9 – 59% 14-19,31,32,33. Concerted efforts to continually stimulate pharmacists’ interest and involvement in pharmacy practice-based research is therefore essential to enhance professional competence and ensure evidence-based practice 12.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 50 % or more of the surveyed hospital and intensive care unit pharmacists reported previous involvement in pharmacy practice research. The interest of pharmacists in participating in research was relatively high and ranged between 40 and 84 % (Carr et al 2011;Perreault et al 2012;Kanjanarach et al 2012;Hébert et al 2013;Elkassem et al 2013;Awaisu et al 2014). Overall, pharmacists agreed on the importance of conducting practice-based research and shared their beliefs that research is part of their professional responsibility and is a critical tool for improving patients' care.…”
Section: -2014mentioning
confidence: 98%
“…The methods for training individuals in skills to conduct pharmacy practice as well as clinical and translational research have been extensively discussed in the literature (Blouin et al 2007;Dowling et al 2009;Knapp et al 2011;Poloyac et al 2011;Smith et al 2009). Most pharmacists in community and hospital practices have limited exposure to clinical and practice research (Awaisu et al 2014;Elkassem et al 2013;Simpson et al 2001). These inadequacies call for intervention.…”
Section: Pharmacists' Attitudes Towards Practice-basedmentioning
confidence: 99%
See 1 more Smart Citation